Cognitive outcomes in children and adolescents born very preterm: a meta‐analysis. (17th February 2018) - Brydges, Christopher R; Landes, Jasmin K; Reid, Corinne L; Campbell, Catherine; French, Noel; Anderson, Mike
Abstract : Aim: To estimate the association between very preterm birth (<32wks' gestation) and intelligence, executive functioning, and processing speed throughout childhood and adolescence, and to examine the effects of gestational age, birthweight, and age at assessment. Method: Studies were included if children were born at earlier than 32 weeks' gestation, aged 4 to 17 years, had an age‐matched term control group, and if the studies used standardized measures, were published in an English‐language peer‐reviewed journal, and placed no restrictions on participants based on task performance. Results: We evaluated 6163 children born very preterm and 5471 term‐born controls from 60 studies. Children born very preterm scored 0.82 SDs (95% confidence interval [CI] 0.74–0.90; p <0.001) lower on intelligence tests, 0.51 SDs (95% CI 0.44–0.58; p <0.001) lower on measures of executive functioning, and 0.49 SDs (95% CI 0.39–0.60; p <0.001) lower on measures of processing speed than term‐born controls. Gestational age and birthweight were associated with study effect size in intelligence and executive functioning of younger children only. Age at assessment was not associated with study effect size. Interpretation: Children born very preterm have medium to large deficits in these cognitive domains. What this paper adds: This meta‐analysis is centred on very preterm birth and three cognitive domains. The three critical cognitive domains are intelligence, executive functioning, and processing speed. What this paper adds: This meta‐analysis is centred on very preterm birth and three cognitive domains. The three critical cognitive domains are intelligence, executive functioning, and processing speed. This review is commented on by Korzeniewski on page436 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.